2021
DOI: 10.3389/fnut.2021.739676
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Methionine Levels in Low Protein Diets on Production Performance, Reproductive System, Metabolism, and Gut Microbiota in Laying Hens

Abstract: This study investigated the effects of different levels of methionine (Met) in a low protein diet on the production performance, reproductive system, metabolism, and gut microbial composition of laying hens to reveal the underlying molecular mechanism of Met in a low protein diet on the host metabolism and gut microbial composition and function of hens. A total of 360 healthy 38-week-old Peking Pink laying hens with similar body conditions and egg production (EP) were randomly divided into four groups with nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…Notably, Dai et al discovered that AA could regulate the composition of the intestinal bacterial population from the small intestine in pigs ( 43 ). In this study, we found that there were no significant differences in alpha diversity indices between NC (Met 0.46%) and Met- group (Met 0.26%), which was similar to the previous study ( 44 ). Wu et al found that D-methionine supplementation had no effects on alpha diversity indices in male Wistar rats (176–200 g, 6 weeks old), who uncovered the Met diet does not alter gut microbiota structure ( 45 ).…”
Section: Discussionsupporting
confidence: 91%
“…Notably, Dai et al discovered that AA could regulate the composition of the intestinal bacterial population from the small intestine in pigs ( 43 ). In this study, we found that there were no significant differences in alpha diversity indices between NC (Met 0.46%) and Met- group (Met 0.26%), which was similar to the previous study ( 44 ). Wu et al found that D-methionine supplementation had no effects on alpha diversity indices in male Wistar rats (176–200 g, 6 weeks old), who uncovered the Met diet does not alter gut microbiota structure ( 45 ).…”
Section: Discussionsupporting
confidence: 91%
“…The methods used for intestinal microbiome analysis were consistent with a previous paper [ 21 ]. Alpha-diversity measure was analyzed using MOTHUR software (1.30.2).…”
Section: Methodsmentioning
confidence: 89%
“…Dietary amino acid deficiencies negatively affect egg production, egg quality, and serum biochemical indices ( Geng et al, 2021 ), and a deficiency of Met affects protein synthesis ( Elango, 2020a ; Liu et al, 2022 ; Teng et al, 2023 ). When animals are healthy, protein synthesis increases, and the serum TP and ALB concentrations also tend to increase ( Ma et al, 2021 ). UA is an end product of catabolism ( Chen et al, 2018 ), and the serum UA concentration reflects the health status of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…UA is an end product of catabolism ( Chen et al, 2018 ), and the serum UA concentration reflects the health status of the animal. Ma et al showed that high dietary Met levels (0.31–0.47%) are associated with greater amino acid utilization and alterations in the serum UA concentration ( Ma et al, 2021 ). As the dietary level of methionine (Met) increased, corresponding increases in the serum concentrations/activities of TP, ALB, and ALP were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation